Analysis of Criminal Crime Responsibility Against Perpetrators of Banking Corruption Crimes - Ternando, Albi (SASI, 2023)
Introduction: The Banks as service providers need to provide maximum service to their customers and protect them from third parties trying to take over part or all of the customers' deposits and trust in the bank. Therefore, banks should regulate and establish procedures and mechanisms for the protection and provide solutions in the event of an action or activity that is detrimental to the customerPurposes of the Research:  Based on the background of the problems described above, it can be formulated the problems that the writer will examine, namely: 1). How is the Criminal Accountability Against the Perpetrators of Banking Corruption Crimes in the City of Jambi? 2). What is the Basis of Consideration of the Panel of Judges to decide on the perpetrators of Banking Corruption Crimes (Case Study of District Court Orders No: 04/ Pid.Sus -TPK/2016/PN. Jmb)Methods of the Research: The research method used was normative research. Based on the results of this study, it was concluded that banking crimes are a canteen of crimes that occur within the scope of banking. The complexity of these crimes causes the prosecution of perpetrators of these crimes to apply the Corruption Crime Act.Results of the Research: The results show that or the findings of this study prove that the basis for the judge's decision for the perpetrators of criminal acts in the District Court decisions are aggravating and mitigating matters as stated in the decision.